f(x)= (x^2 -1)/(x^2 + 1)

Let f(x) = u/v such that:

u = (x^2 -1) ==> u' = 2x

v= x^2 + 1 ==> v' = 2x

==> f'(x)= (u'v-uv')/v^2

= (2x(x^2 + 1) - (x^2 -1)2x ]/(x^2 +1)^2

= (2x^3 + 2x - 2x^3 + 2x)/(x^2+1)^2

= 4x/(x^2 + 1)

==> f'(x) = 4x/(^2 + 1)^2

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now